Analisis Proksimat pada Produk Pangan Fungsional Kerupuk Jamur Tiram Coklat (Pleurotus cystidiosus) dengan Variasi Metode Pemasakan Menggunakan Minyak dan Pasir - Anne Yuliantini; Emma Emmawati; Yuni Kartika (Jurnal Pangan dan Gizi, 2026)
Crackers are a popular food, but are often considered to have low nutritional value. An innovation involving the addition of brown oyster mushrooms, which are rich in protein and antioxidants, was carried out to increase their nutritional content. This study aims to analyze the nutritional content of crackers based on cooking methods, namely using oil and without oil. The analysis conducted includes sensory analysis (hedonic test) and proximate analysis (moisture, ash, fat, protein, carbohydrate, and crude fiber content). The hedonic test results showed that crackers fried with oil were preferred by panelists because of their taste and texture. However, in terms of nutritional value, crackers fried without oil had a higher value. The results of the proximate analysis showed that crackers cooked using oil contained 4.41% moisture, 2.22% ash, 2.79% fat, 5.99% protein, 84.46% carbohydrates, and 4.43% crude fiber. Meanwhile, crackers cooked using sand contained 6.75% moisture, 2.79% ash, 6.13% protein, 78.05% carbohydrates, and 4.69% crude fiber. The cooking method has a significant effect on nutritional content, where cooking without oil tends to increase protein, carbohydrate, and crude fiber content. Meanwhile, cooking with oil increases fat and ash content and decreases moisture content.